Le pop art : dictionnaire de poche. - Pierre, José (Paris : Fernand Hazan, 1975)
Adami, Valerio ; Adzak, Roy ; Agostini, Peter ; Agullo, Thierry ; Alleyn, Edmund ; Alvermann, Hans Peter ; van Amen, Woody ; Apple, Billy ; Arakawa, Shusaku ; Arman ; Arneson, Robert ; Artschwager, Richard ; Axell, Evelyne ; Baj, Enrico ; Barker, Clive ; Baruchello, Gianfranco ; Bengston, Billy ; Berlant, Anthony ; Berman, Wallace ; Bertholo, René ; Bertini, Gianni ; Beynon, Eric ; Blake, Peter ; Boshier, Derek ; Brecht, George ; Brüning, Peter ; Buri, Samuel ; Cage, John ; Canogar, Rafael ; Castro, Lourdes ; Caulfield, Patrick ; Cavaliere, Alik ; César ; Cheval-Bertrand ; Christo ; Collins, Jess ; Conner, Bruce ; Curnoe, Greg ; D'Arcangelo, Allan ; Pezzo, Lucio Del ; Deschamps, Gérard ; Dietmann, Erik ; Dine, Jim ; Suvero, Mark di ; Donaldson, Anthony ; Drexler, Rosalyn ; Duchamp, Marcel ; Dufo, Alain ; Dufrêne, François ; E.A.T. ; Equipo Cronica ; Errò ; Fahlström, Öyvind ; Flexner, Roland ; Foulkes, Llyn ; Francken, Ruth ; Frazier, Charles ; Gasiorowski, Gérard ; Gette, Paul-Armand ; Gilardi, Piero ; Gill, James ; Gilli, Claude ; Gnoli, Domenico ; Goode, Joe ; Graham, Robert ; Grisi, Laura ; Grooms, Red ; Guyomard, Gérard ; Hains, Raymond ; Hamilton, Richard ; Haworth, Jann ; Hedrick, Wally ; Hefferton, Phillip ; Hockney, David ; Indiana, Robert ; Jacquet, Alain ; Johns, Jasper ; Johnson, Ray ; Jones, Allan ; Kaprow, Allan ; Kermarrec, Joël ; Kienholz, Edward ; Klapheck, Konrad ; Klasen, Peter ; Laing, Gerald ; Lichtenstein, Roy ; Lindner, Richard ; Lundberg, L.G. ; Maglione, Milvia ; Malaval, Robert ; Manzoni, Piero ; Mara, Pol ; Marchi, Graziella ; Mariani, Umberto ; Marisol ; Maselli, Titina ; Meister, Jean-Marie ; Melchert, James ; Messac, Ivan ; Messager, Annette ; Miki, Tomio ; Minujin, Marta ; Miralda, Antoni ; Monory, Jacques ; etc.
Biog. per kunstenaar
Frans
boek